2016
DOI: 10.5539/jas.v9n1p49
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Expression Profiling of Seedling Stage in Early-Maturity Mutant Induced by Carbon Ion Beam in Sweet Sorghum

Abstract: An early-maturity mutant KFJT-1 has been screened out after carbon ion irradiation in sweet sorghum (Sorghum bicolor (L.) Moench). In this study, tissue specific digital gene expression analysis was performed between the KFJT-1 mutant and the wild type KFJT-CK at seedling stage. The results showed that a total of 717, 2160 and 2,331 tags-mapped genes were differently expressed in roots, stems and leaves of young seedling, respectively. In KFJT-1, 557 (77.7%) genes were up-regulated and 160 (22.3%) genes were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…To obtain a global view of the tissue specific characteristics at the transcriptional level between KFJT-1 and KFJT-CK at seedling stage, total six DGE libraries from roots, stems and leaves were sequenced with Solexa/Illumina DGE analysis, respectively (Dong et al, 2017). In root, a total of 557 genes were up-regulated and 160 genes were down-regulated.…”
Section: Expressmentioning
confidence: 99%
“…To obtain a global view of the tissue specific characteristics at the transcriptional level between KFJT-1 and KFJT-CK at seedling stage, total six DGE libraries from roots, stems and leaves were sequenced with Solexa/Illumina DGE analysis, respectively (Dong et al, 2017). In root, a total of 557 genes were up-regulated and 160 genes were down-regulated.…”
Section: Expressmentioning
confidence: 99%
“…Moreover, our study indicated that KFJT-1 was able to not only flower but also produce mature grain, which an insert fragment GA was found in KFTJ-1 and the corresponding fragment was not found in KFJT-CK for the Hd3a gene by further research (Dong et al, 2015). Functional analysis of gene ontology indicated that genes involved flowering time were also enriched such as "response to far red light", "pollen development" including "auxin transport", which consist with the short growth cycle of KFJT-1 compared to KFJT-CK (Dong et al, 2017). At present, KFJT-1 has been identified by the Gansu provincial variety Approval Committee after regional trial and production test for several years , which can solve the difficult problem of earlier frost during industrialization plant for bio-ethanol production using sweet sorghum as feedstock in the northwest region of China.…”
Section: Improvement Of Sweet Sorghum Varietymentioning
confidence: 93%
“…Using DNA microarray techniques, Hwang et al (2014) found that 220 MeV l À1 carbon ions (LET = 107 keV l À1 ) can induce up-regulated gene expression related to sugar and starch accumulation in rice. In another study by Dong et al (2016b), an early-maturity sweet sorghum mutant KFJT-1 has been obtained after carbon ion irradiation; through comparative gene expression analysis between the KFJT-1 mutant and the wild-type KFJT-CK, the down-regulated PHYA gene was conferred to result in high sucrose content accumulation in KFJT-1. However, combined omics assays and the promising microbial mutants induced by heavyion irradiation to investigate the involved mechanisms have not been reported.…”
Section: High-throughput System For Screening Positive Microbial Strainmentioning
confidence: 99%